Pengaruh Marketing Mix, Customer Relationship Management Dan Pengalaman Pelanggan Terhadap Keputusan Pembelian (Studi Kasus Pada Grosir Snack Bu Dewi di Kab Mojokerto) - Putra, Rivaldy Danendra; Mahsuni, Abdul Wahid; Novianto, Abdullah Syakur (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of the Marketing Mix, Customer Relationship Management, and Customer Experience on Purchasing Decisions at Bu Dewi Snack Wholesaler in Mojokerto Regency. The application of the marketing mix, customer relationship management, and customer experience to each of these variables not only contributes individually but also collectively to shaping consumer preferences and behavior in an era of increasingly competitive business. The research method used in this study is a quantitative approach with data collection techniques in the form of online and offline questionnaires distributed to 85 customers of Bu Dewi Snack Wholesaler. The results of this study indicate that the marketing mix has a positive and significant effect on purchasing decisions, customer relationship management has a positive and significant effect on purchasing decisions, and customer experience has a positive and significant effect on purchasing decisions. The implications of this study explain that Bu Dewi Snack Wholesaler needs to apply the marketing mix, customer relationship management, and customer experience to purchasing decisions in order to create a combined marketing strategy that encompasses product management, pricing, promotion implementation, and customer relationship management that can encourage consumers to make purchases. Keywords: Marketing Mix, Customer Relationship Management, Customer Experience, Purchasing Decision, Bu Dewi Snack Wholesaler